2018
DOI: 10.1007/s00220-017-3070-z
|View full text |Cite
|
Sign up to set email alerts
|

A Conformally Invariant Gap Theorem in Yang–Mills Theory

Abstract: We show a sharp conformally invariant gap theorem for Yang-Mills connections in dimension 4 by exploiting an associated Yamabe-type problem.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…It is easy to see that the expression γ 1 (E)|F | is independent of the choice of norms. Therefore, despite the difference of conventions pointed out in Remark 3.5, the definition of Φ g in (3.9) agrees with the corresponding formula (3.5) in [GKS18].…”
Section: A Canonical Conformal Representativesupporting
confidence: 75%
See 2 more Smart Citations
“…It is easy to see that the expression γ 1 (E)|F | is independent of the choice of norms. Therefore, despite the difference of conventions pointed out in Remark 3.5, the definition of Φ g in (3.9) agrees with the corresponding formula (3.5) in [GKS18].…”
Section: A Canonical Conformal Representativesupporting
confidence: 75%
“…Proof. Using the Bochner formula for Yang-Mills connections, in [GKS18] we showed that either F + ≡ 0, or else λ 1 (L g ) = λ 1 (L 1 g ) ≤ 0. Since we are ruling out the former by assumption, the latter condition must hold.…”
Section: A Canonical Conformal Representativementioning
confidence: 90%
See 1 more Smart Citation
“…This result is a combination of classical results [2,7] concerning energy minimizing solutions within a topological class (called instantons), as well as a recent energy lower bound for the non-minimizing solutions proved by Gursky-Kelleher-Streets [16]. For a derivation, see [39,Section 6].…”
Section: Such a Function O Induces The Gauge Transformationmentioning
confidence: 53%
“…On the other hand, the question of existence of finite energy harmonic Yang-Mills connections is best phrased in terms of the topological classes described above: Parts (1) and (2) are classical. We remark that part (3), which follows from a recent result of [8], is nontrivial due to existence of nonminimizing harmonic Yang-Mills connections [39]. We also note that harmonic Yang-Mills connections which are not energy minimizers no longer have to be self-dual or anti-self-dual.…”
Section: Topological Classes Of Finite Energy Connections On Rmentioning
confidence: 71%